Troubled childhoods cast long shadows: Childhood adversity and premature all-cause mortality in a Swedish cohort - Josephine Jackisch; Lars Brännström; Ylva B. Almquist (Elsevier, 2019)
Experiences of childhood adversity are common and have profound health impacts over the life course. Yet, studying health outcomes associated with childhood adversity is challenging due to a lack of conceptual clarity of childhood adversity, scarce prospective data, and selection bias. Using a 65-year follow-up of a Swedish cohort born in 1953 (n = 14,004), this study examined the relationship between childhood adversity (ages 0-18) and premature all-cause mortality (ages 19-65). Childhood adversity was operationalized as involvement with child welfare services, household dysfunction, and disadvantageous family socioeconomic conditions. Survival models were used to estimate how much of the association between child welfare service involvement and mortality could be explained by household dysfunction and socioeconomic conditions. Results show that individuals who were involved with child welfare services had higher hazards of dying prematurely than their majority population peers. These risks followed a gradient, ranging from a hazard ratio of 3.08 (95% CI: 2.68-3.53) among those placed in out-of-home care, followed by individuals subjected to in-home services who demonstrated a hazard ratio of 2.53 (95% CI: 1.93-3.32), to a hazard ratio of 1.81 among those investigated and not substantiated (95% CI: 1.55-2.12). Associations between involvement with child welfare services and premature all-cause mortality were robust to adjustment for household dysfunction and disadvantageous family socioeconomic conditions. Neither household dysfunction nor socioeconomic conditions were related with mortality independent of child welfare services involvement. This study suggests that involvement with child welfare services is a viable proxy for exposure to childhood adversity and avoids pitfalls of self-reported or retrospective measures. Keywords: Sweden, Premature mortality, Cohort study, Adverse childhood experiences, Childhood social conditions, Longitudinal, Child welfare